Single-Cell RNAseq Resolve the Potential Effects of LanCL1 Gene in the Mouse Testis - Jiangting Lu; Jinling Liao; Min Qin; Hui Li; Qingyuan Zhang; Yang Chen; Jiwen Cheng (Cells, 2022)
Infertility affects lots of couples, half of which are caused by male factors. The LanCL1 gene is highly expressed in testis specifically, which might affect the development of sperms. In order to understand the potential functions of the LanCL1 gene in the testis, this study was conducted with constructed transgenic LanCL1 knockout mice. The mouse breeding experiment, semen analysis and single-cell RNAseq of testicular tissue were performed. Results suggested that the LanCL1 gene would significantly influence the reproduction ability and sperm motility of male mice. Single-cell RNAseq also confirmed the high expression of the LanCL1 gene in the spermatocytes and spermatids. Downregulating the LanCL1 gene expression could promote M2 macrophage polarity to maintain testicular homeostasis. Moreover, the LanCL1 gene could affect both the germ cells and stromal cells through various pathways such as the P53 signaling and the PPAR signaling pathway to disturb the normal process of spermatogenesis. However, no effects of the LanCL1 gene in testosterone synthesis and serum testosterone level were shown. Further studies are needed to discuss the mechanisms of the LanCL1 gene in the various cells of the testis independently.